2007
DOI: 10.1371/journal.pone.0001006
|View full text |Cite
|
Sign up to set email alerts
|

SIRNA-Directed In Vivo Silencing of Androgen Receptor Inhibits the Growth of Castration-Resistant Prostate Carcinomas

Abstract: BackgroundProstate carcinomas are initially dependent on androgens, and castration or androgen antagonists inhibit their growth. After some time though, tumors become resistant and recur with a poor prognosis. The majority of resistant tumors still expresses a functional androgen receptor (AR), frequently amplified or mutated.Methodology/Principal FindingsTo test the hypothesis that AR is not only expressed, but is still a key therapeutic target in advanced carcinomas, we injected siRNA targeting AR into mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 44 publications
6
64
0
Order By: Relevance
“…The most pertinent question was whether TRPV2 silencing could inhibit tumor development in vivo. Previously, a RNA interference in vivo has been used to show that the androgen receptor is still required for the development of castration-resistant prostate tumors (25). Similarly, the model of mice bearing xenografted PC3 cell-provoked tumors has been created.…”
Section: Resultsmentioning
confidence: 99%
“…The most pertinent question was whether TRPV2 silencing could inhibit tumor development in vivo. Previously, a RNA interference in vivo has been used to show that the androgen receptor is still required for the development of castration-resistant prostate tumors (25). Similarly, the model of mice bearing xenografted PC3 cell-provoked tumors has been created.…”
Section: Resultsmentioning
confidence: 99%
“…First, we determined whether the systemic delivery of siRNA by i.p. injection could reduce CEACAM6 expression and enhance viral replication in a subcutaneous Suit-2 xenograft tumor model (25). Delivery of CEACAM6-specific siRNA by i.p.…”
Section: A Suitable Cell Model For Screening Tumor-associated Genes Amentioning
confidence: 99%
“…Treatments with PBS, control siRNA, and CEACAM6 siRNA were administered on day 1, 2, and 3 by i.p. infection as described previously (25). For assessment of viral replication in vivo, 1 × 10 10 pt of replicating adenovirus vector expressing red fluorescent protein in 50 μl was injected intratumorally on day 4 after each injection of siRNAs and PBS.…”
Section: Evaluation Of Viral Replication and Antitumor Efficacy Of Admentioning
confidence: 99%
“…Androgen/AR signaling is required for androgensensitive LNCaP cells to proliferate. Yang et al [12] and Compagno et al [13] reported that the use of small interfering RNA (siRNA) to suppress endogenous AR in LNCaP cells led to apoptosis without proliferation. Similar results were also reported by Liao et al [14] and Haag et al [15].…”
Section: Lncap Cellsmentioning
confidence: 99%